Influencia de la estabilidad del gobierno sobre la deuda externa de la economía Ecuatoriana, durante el periodo de 1990 - 2020 - Poma Torres, Noelia del Carmen (2023)
Debt can be a blessing or a nightmare, the quantity is irrelevant, the quality of the government is the most important factor. In recent years, Ecuador has exceeded the legal debt ceiling, by 2021 it had a debt of USD 47,855 millions, which represents 45.4% of its GDP. In this sense, this work is projected to evaluate the influence of goverment stability of Ecuador’s external debt during the period 1990 - 2020, through a statistical and, econometric analysis of time series, in order to propose mechanisms aimed at reducing high external debt. For this purpose, data from the World Bank (2021), Central Bank (2020), The Worldwide Governance Indicators (2020) and Pen World Table (2020) are used, where cointegration and causality tests are applied. It can be highlighted that the goverment stability has a positive casual relationship at long term on external debt, while the control variables, natural resource rent, and human capital have a negative casual effect on the external debt, so that, at finding booming the variables mentioned, they will contribute to minimize external debt at long term. In view of this, it is proposed to improve the formal and explicit public debt management strategy, based on sustainable fiscal management and to have reserve funds as a political alternative, in order to save in times of prosperity and dispose of them in times of illiquidity.